(untitled) (Research, Society and Development, 2022)
Objective: To report the clinical management of a patient with Diabetic Ketoacidosis (DKA), from the a literature review about the theme. Methods: Case study, analyzing treatment protocols about the correlation of the effectiveness of the correction of Ketoacidosis with the incidence of complications secondary to the respective treatment in a patient hospitalized in Pediatric Unit. Results: The patient presented DKA in first decompensation. The reduction speed of blood glucose in the first hour was superior to 100 mg/dL/hour, and the HGT data from the subsequent hours up to the eighth hour of treatment in the medical records were not found. Variable concentrations of glucose and potassium in the plan for basic water and electrolyte needs were utilized within the first 24 hours. The infusion of intermediate NPH began 36 hours after the start of the treatment. Regarding data complications, it was observed that the patient presented hypoglycemia, hypopotassemia, persistence of metabolic acidosis by early withdrawal of regular insulin infusion, with subsequent alkalosis due to the use of bicarbonate in the correction of acidosis. Conclusion: After data collection and analysis in the light of the theoretical reference framework, it was observed the non-existence of a specific protocol to the DKA treatment in the studied service, being that the use of these protocols help in the adequate treatment of the acute complication of diabetes, which avoids a greater risk of complications and reduces morbimortality.